Learning from directors' foreign board experiences - Iliev, Peter; Roth, Lukas (Journal of Corporate Finance, 2018)
We study the transfer of governance across countries through overlapping international boards. Companies converge to the governance characteristics and board practices of foreign firms through their directors' foreign board experiences. Learning from foreign firms' governance practices is as important as learning from connected domestic firms, and increases with the number of directors with foreign board appointments. This learning channel is stronger for firms domiciled in less-developed governance markets, suggesting a potential mechanism through which better governance practices are propagated. Our results are obtained in the time series and do not exist in placebo samples.